The legacy of African kimberlite and diamond research and exploration for the earth sciences - Moore, Andy; Helmstaedt, Herwart (Herb); Bamford, Marion (Journal of African earth sciences (1994), 2024)
Kimberlite is a rare and volumetrically insignificant magmatic rock, which nevertheless has an outsized economic importance as the world's principal source for natural diamonds. Discovered in 1870, in South Africa, it was named after Kimberley, the town that grew around the first mines developed in the pipe-shaped bodies of the newly discovered, ultramafic diamond source rock. Apart from their economic significance, kimberlites are of enormous scientific interest. Originating at great depth, they have entrained a variety of ultramafic and ultrabasic rock fragments (xenoliths) and their disaggregated mineral grains (xenocrysts) that provide a direct window into the upper mantle, making it possible to identify regional variations in the nature of the upper mantle and to understand mantle processes. After a flurry of studies on the heels of the initial kimberlite discoveries, there was a long hiatus in publications between the 1930's and mid-1960's. Kimberlite, diamond, and upper mantle studies received a lasting stimulus in the early 1970's, largely as the result of the seminal First International Kimberlite Conference (1 IKC), held at the University of Cape Town in 1973, and 10 follow-up conferences held since on every continent except Antarctica. This review explores examples of advances and controversies resulting from African-centered research on the subject. The definition and nomenclature of “kimberlite” progressed from applying the term to all igneous rocks with diamond, to distinguishing two types of diamond-bearing kimberlite (Groups I and II), and eventually recognizing that Group I (“archetypal” kimberlite) and Group II (formerly orangeite, now assigned to the olivine lamproite clan) are entirely different rock types, originating below and within the lower part of the lithosphere, respectively. As to the shape of kimberlite pipes, the classic southern African model of a carrot-shaped magmatic system, consisting of a root zone, a steep-sided diatreme, and a crater zone, was based on a composite of the highly eroded Kimberley and Jagersfontein pipes, for the lower part, and the significantly less eroded Orapa pipe in Botswana, for the upper part. Restriction of diamond-bearing igneous rocks to the ancient cratons of Africa led to the formulation of “Clifford's Rule”, an important tool in diamond exploration worldwide. Studies of peridotite xenoliths and Mesoarchean ages determined on peridotitic garnet inclusions in diamond xenocrysts from the Kaapvaal craton revealed that the craton is underlain by a deep diamondiferous lithospheric root which is older, cooler, and more refractory (harzburgitic) than the shallower lithosphere under adjacent Proterozoic orogenic belts, in fact providing a petrologic explanation for Clifford's rule. The correlation between harzburgitic garnet and diamond was expanded into a powerful exploration tool, developed, and tested in Africa, that was successfully applied in many other parts of the world. Interpretations of eclogite xenoliths changed from being cognate nodules in kimberlite, to pieces of an eclogite layer, to high-pressure cumulates from eclogitic melts in a peridotitic mantle, to fragments of subducted oceanic crust. Combining the latter interpretation with Archean ages for eclogitic mineral inclusions in diamond xenocrysts, it was recognized that plate tectonic processes began as early as ca. 2.9 Ga and were involved in the formation of the Kaapvaal craton, the oldest major Archean craton in the world. Based on the model developed for typical kimberlite pipes in southern Africa, it has been possible to quantify erosion processes across the southern part of the continent, particularly since the disruption of Gondwana. Dispersion of “pathfinder” kimberlitic indicator minerals (KIMs), including diamond, into drainage networks provide tracers to reconstruct past river systems. Being well endowed with kimberlite pipes, Africa has also been central to the important debate about the relevance of plumes as triggers for kimberlite and other alkaline magmatism. Nevertheless, despite the importance of resolving this geological conundrum, it remains highly controversial. Many kimberlites are capped by well-preserved crater-lake facies sediments, most of which are dated as Cretaceous to early Cenozoic, within the time of the proposed Angiosperm Terrestrial Revolution. As the associated plant fossil records are the only ones for the interior of southern Africa during this time interval, they may contribute to solving what has been coined as “Darwin's Abominable Mystery”, the poorly understood origin of angiosperms (flowering plants). •Mantle Petrography and Processes.•Diamonds.•Kimberlite target selection.•Geomorphology; Palaeontology.